Ethiopia : Education in Ethiopia, Strengthening the Foundation for Sustainable Progress - World Bank (Washington, DC, 2012)
Despite daunting difficulties in Ethiopia, the optimism today about the country's future is palpable. The government has made poverty reduction the centerpiece of its development strategy, and it has continued to advance the reform of governmental structure, functions, and finances. These contextual factors are highly pertinent for education. The Poverty Reduction Strategy Paper (PRSP) envisions a key role for the sector, placing on it the following expectations: progress toward universal primary education; improvement in the quality of services throughout the system; and, the production of a trained workforce, responsive in quantity and skills mix, to the demand for educated labor in the country's modernizing economy. For the education sector, these features in the country's political and economic landscape prompt a host of questions: Is the current education policy framework adequate for fulfilling the expectations placed on the sector? What resources are available to achieve the stated goals? Are these sufficient to meet the requirements? If not, how will the gap between resource availability and need be closed? What changes in the financing of education, in resource allocation across sub-sectors and schooling inputs, and in the arrangements for service delivery will help ensure that the education system develops over the long run in a fiscally viable and pedagogically sound manner? This report serves as a contribution to the continuing dialogue on these strategic questions regarding the goals of, and means for education sector development. The report provides a snapshot of the education sector up to 2001-02 (and, on some dimensions, up to 2002-03). Its intent is to portray selected aspects accurately, to discover potentially important areas for policy development. The report is thus deliberately diagnostic in orientation. The analysis in this report yields findings that are relevant for discussing the potential scope for improvement; below some of these findings suggest to: Universalize four years of schooling as an immediate priority; Adapt the goals for coverage, to conditions in urban and rural areas; Allow labor market conditions to guide the pace of expansion beyond wade 4; Improve the education system's responsiveness to labor market signals; Prioritize education, especially primary education, in the allocation of public spending; Choose fiscally sustainable standards that benefit the system as a whole; Support alternative basic education centers as an option for service delivery; Accept flexible standards in order to lower costs in the formal school system; Keep the set of indicators for primary education small and relevant; Improve the availability and accessibility of schools in rural areas; Deploy teachers across schools in relation to the size of enrollments; and, Encourage schools to progressively offer complete instructional programs.